PRONATEC e a evasão escolar nos cursos de Formação Inicial e Continuada (FIC) no IFMT – Campus Cuiabá Cel. Octayde Jorge da Silva – 2013 - Silva, Marcos André da (2015)
The National Program for Access to Technical Education and Employment (PRONATEC) was created in order to democratize and expand vocational and technical education to all citizens by offering free training courses and quality for the Brazilian population, especially those who are in vulnerable social. This program, created by the Federal Government proposes to increase the number of places and scholarships to interested parties, giving priority to students who have completed Mediun Teach in the public or as a full scholarship from the private network. With regard to workers, although aware of the need to conduct training, not always seek for themselves that learning due to different factors ranging from the political, educational as individuals. The lack of preparation for the current labor market, make it more difficult for the worker himself the conquest of a good job, generates for the business sector losses, because they are in need of skilled labor and not getting a qualified professional that meets the requirements the current market. On the other side, what has been observed on the ground is that truancy has occurred at a very significant rate in PRONATEC courses, especially in the FIC mode. This work has as object of study, specifically at the problem of truancy in the courses of Initial and Continuing (FIC) of this Program, offered by the Federal Institute of Education, Science and Technology - IFMT - Campus Cuiabá Cel. Octayde Jorge da Silva in 2013. We sought to identify the main causes of abandonment of education by the student, knowing what the school has done to reverse the state and at the same time, submit proposals for the permanence and continuity of studies for the promotion and social mobility of students of the course. The research is configured as Qualitative and Quantitative, with the application questionnaire and semi-structured individual interviews with managers, teachers and students of six (6) courses offered this year, aiming to contribute to analysis for the PRONATEC. It has become clear that the causes of dropout are varied, competitors and non-exclusive. It must propose concrete policies to decrease this problem.